Pre-cooling for football training and competition in hot and humid conditions - Duffield, R.; Coutts, A.; McCall, A.; Burgess, D. (European Journal of Sport Science, 2013)
Pre-cooling studies report positive physiological and performance benefits in laboratory conditions, although research studies have not investigated these reported benefits in ecologically valid team-sport training and competition settings. Accordingly, this study investigated the effect of field-based pre-cooling strategies for professional football players during training and competition in the heat. Ten professional football players from an Australian A-League club performed two training sessions and competitive matches in hot ambient conditions (29±3oC, 78±8% relative humidity) with or without pre-cooling. The pre-cooling intervention involved 20-min of an ice-vest, cold towels and 350 mL ice-slushie drink. Training sessions (n=9) were randomised, and consisted of 2 x 10-min interval training, followed by 6 x 3-min of 5v5 small sided games. Competitions (n=7) involved official A-League matches during the 2009-10 season. Player movement characteristics, core temperature (gastrointestinal), skin temperature, nude mass, heart rate, capillary blood (glucose, K+, Na+, haematocrit), perceptual exertion and thermal stress measures were recorded. No significant differences (P>0.05) were present between conditions for any measure of physical performance, although moderate-large effects for a greater total and relative distance covered during training were present (d > 0.8). While mean skin temperature was reduced following cooling, core temperature was only lower until following the warm-up in training and was even less evident during matches (P>0.05; d < 0.6). However, a smaller change in mass (sweat loss) and reduced perceptual exertion and thermal stress were evident during training following cooling (d > 0.9), although again, to a much lesser extent in matches (d = 0.6). In conclusion, equivocal findings were present for the effects of pre-cooling for professional football players during competitive training and matches in the heat. However, performance and thermoregulatory response trends showed similarities to previous laboratory evidence. The field-based nature of the current study may highlight that the transfer of lab findings to field settings is difficult or the strength of the intervention is diminished by the settings.